2019
DOI: 10.1002/fsn3.975
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clove (Syzygium aromaticum) and seaweed (Kappaphycus alvarezii) water extracts pretreatment on lipid oxidation in sun‐dried sardines (Rastrineobola argentea) from Lake Victoria, Tanzania

Abstract: Small indigenous fish species play a significant role in food and nutritional security of poor communities in developing countries. Sardines ( Rastrineobola argentea ) are fish species of Lake Victoria known to be a good source of health‐promoting omega‐3 fatty acids. Open sun drying is a common and traditional sardine processing and preservation method. Sun‐dried products suffer from characteristic off‐flavor due to lipid oxidation which discourage product consumption and limit diversif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
1
5
0
1
Order By: Relevance
“…Liquid waste from LSS (3 g/L) treatment contained TFC (0.04 mg/g) and TPC (0.09 mg/g) and was attributed to high ABTS • (94.33%) and DPPH • inhibition (56.86%) (Table 2). Chaula et al (2019) reported that scavenging activities of K. alvarezii water extracts inhibited DPPH • by 29.67-50.56%. Plants, when stressed, tend to produce more reactive oxygen species (ROS) as by-products of aerobic metabolism, but they simultaneously employ antioxidant metabolites (Table 2) to prevent possible oxidative damage (Apel & Hirt, 2004).…”
Section: Biological Properties Of Dsp Src and Waste-seawater Productmentioning
confidence: 99%
“…Liquid waste from LSS (3 g/L) treatment contained TFC (0.04 mg/g) and TPC (0.09 mg/g) and was attributed to high ABTS • (94.33%) and DPPH • inhibition (56.86%) (Table 2). Chaula et al (2019) reported that scavenging activities of K. alvarezii water extracts inhibited DPPH • by 29.67-50.56%. Plants, when stressed, tend to produce more reactive oxygen species (ROS) as by-products of aerobic metabolism, but they simultaneously employ antioxidant metabolites (Table 2) to prevent possible oxidative damage (Apel & Hirt, 2004).…”
Section: Biological Properties Of Dsp Src and Waste-seawater Productmentioning
confidence: 99%
“…Вільні радикали значною мірою утворюються у морських водоростях, що зазнають дії світла та кисню як фотосинтезуючі організми. Це, в свою чергу, стимулює синтез багатьох протиоксидантних метаболітів для подолання пошкоджень внаслідок окислення (Chaula et al, 2019). Triphati et al (2019) повідомляють про використання лікопену з морських водоростей -каротиноїдного пігменту з протиоксидантною властивістю, в десять разів більшою, ніж мають альфа-токоферол, сечова кислота та екстракт зеленого чаю, які є активними сполуками у боротьбі із запаленням ясен.…”
Section: протимікробна активність щодо патогенних мікробів ротової порожниниunclassified
“…Lower concentrations of such compounds in pre-treated samples imply that the nutritionally valued PUFAs DHA and EPA were protected against oxidative damage during storage. Clove water extracts have been reported to retard lipid oxidation during sun-dry processing of sardines resulting into lower concentrations of volatile compounds in dry sardines [27]. Phenolic compounds are known to exert anti-oxidative effect by different mechanisms such as scavenging of free radicals, singlet oxygen quenching, oxygen scavenging, metal chelation and inhibition of oxidizing enzymes [21,22].…”
Section: Primary and Secondary Lipid Oxidation Productsmentioning
confidence: 99%
“…Elsewhere, the clove water extract has been found to contain substantial amounts of phenolic compounds and powerful antioxidant activity in linoleic acid emulsion [26]. Clove water extracts are reported to result in improved retention of nutritionally valued long chain PUFAs DHA, EPA and DPA during open sun and oven drying of sardines [27,28]. The aim of the current study was to evaluate the efficacy of clove (Szygium aromaticum) water extracts in protecting omega-3 fatty acids during extended storage of sun dried sardines.…”
Section: Introductionmentioning
confidence: 99%